Empowering Indonesia's Halal Cosmetics: Strategies for Industry Development - Cahyania Nursyabani; Nurwahidin (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The halal cosmetics industry is experiencing significant growth and increasing consumer demand for products that meet halal standards. With the majority of Indonesia's population being Muslim, Indonesia has great potential to become a global leader in the production of halal cosmetics. Meanwhile, existing research primarily focuses on consumer behaviour in the halal cosmetics market. This study aims to formulate strategies to accelerate Indonesia's halal cosmetics industry. Literature studies from various scientific sources relevant to the research objectives are analysed using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis framework. The results showed that five strategies could be implemented to accelerate the halal cosmetics industry in Indonesia, including 1) Clarifying regulations, standardisation, and policies; 2) Developing and empowering the halal cosmetics industry; 3) Performing product differentiation and marketing; 4) Developing human resources; and 5) Increasing public literacy. With the implementation of appropriate strategies, Indonesia's halal cosmetics industry is expected to accelerate significantly in the next few years.